Countering the conceits of the Anthropos: scaling down and researching with minor players. Issue 3 (3rd May 2020) - Taylor, Affrica
ABSTRACT: The naming of the Anthropocene (or epoch of Man) portends precarious futures for twenty-first century children. In deciding how best to respond, feminist scholars warn against perpetuating the heroicism and grandiosity of Man-to-the-rescue scripts. Instead they suggest paying close attention to what is already going on in the world beyond the dominion of Man, and refiguring our place in this more-than-human world by telling different kinds of stories. The author responds by recounting minor stories from a common worlds research project about a group of young Australian children's confronting encounters with wild European rabbits. These stories illustrate how assumed-to-be minor players are quietly getting on with the job of inheriting and cohabiting damaged worlds without recourse to human heroicism and dominion. She argues that by scaling down, researching and thinking with minor players outside of the main game, childhood studies is well positioned to counter the conceits of the Anthropos.